2001
DOI: 10.1021/ma0021489
|View full text |Cite
|
Sign up to set email alerts
|

A Phase Diagram for the Binary Blends of Nearly Symmetric Diblock Copolymers. 1. Parameter Space of Molecular Weight Ratio and Blend Composition

Abstract: A phase diagram as a function of molecular weight ratio and blend composition was constructed for the binary blends of nearly symmetric polystyrene-block-polyisoprene (PS−PI) copolymers. In this study we prepared four series of binary blends, and every blend consists of a copolymer, hereafter designated as α, whose number-average molecular weight (M n) and volume fraction of PS-block (f PS) are 1.0 × 105 and 0.47, respectively. Four PS−PI copolymers (hereafter designated β), each of which is blended with α, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
125
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(141 citation statements)
references
References 36 publications
13
125
3
Order By: Relevance
“…Studies show that blends of two AB diblock copolymers exhibit a much richer phase behavior than each neat constituent diblock copolymer. [6][7][8][9][10][11][12][13][14][15][16] This behavior is attributed to the large number of controlling parameters, including those for each constituent copolymers and the blending composition, as well as to the possibility of macrophase separation which is not encountered in the neat system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that blends of two AB diblock copolymers exhibit a much richer phase behavior than each neat constituent diblock copolymer. [6][7][8][9][10][11][12][13][14][15][16] This behavior is attributed to the large number of controlling parameters, including those for each constituent copolymers and the blending composition, as well as to the possibility of macrophase separation which is not encountered in the neat system.…”
Section: Introductionmentioning
confidence: 99%
“…In the first series, the constituent diblock copolymers of the blend both have nearly symmetric compositions but rather different molecular weights. 7,[9][10][11] In the second series, the constituent diblock copolymers have almost the same molecular weights but complementary compositions. 12 In the third series, the constituent diblock copolymers were composed of a long asymmetric copolymer having a spherical (or cylindrical) morphology and a short symmetric copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of the possible ordered structures for the binary blends of BCPs is schematically illustrated in Figure 9 (based on Hashimoto et al). [42] Similarly, the possibility that both I and II are in the ordered phase, forming either (4) two macroscopically phase-separated structures as illustrated in Figure 9(b) or (5) a single-phase structure as given in Figure 9(c) is also almost out of the question due to the data given in Figure 7 and 8. The only remaining possibility (3), i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The following five possible states of the I/II blend could be considered: [42] Both BCPs I and II are in the disordered phase, forming either (1) a single phase or (2) two phases, (3) I and II are phase-separated with II in the ordered phase and I in the disordered phase, or both I and II are in the ordered phase, forming either (4) two macroscopically phase-separated structures or (5) a single-phase structure. We expected a gradual transition from (3) to (5) from the properties of individual components I and II.…”
Section: Resultsmentioning
confidence: 99%
“…[46] A series of microphase transition studies on binary blends of polystyrene-block-polyisoprene (SI) diblock copolymers have the phase behavior proven to dissent often from the one-component approximation. [47][48][49] Liu et al [50] used the self-consistent field theory to determine in a phase diagram the relative stability of different Frank-Kasper phases for binary blends of AB diblock copolymers. This study revealed large regions for the Frank-Kasper phases, especially for the σ phase, and confirmed thereby blending as a novel route to complex structures.…”
Section: Introductionmentioning
confidence: 99%